Assessment of the analgesic potential of ethylacetate leaf fraction of Sida linifolia L. (Malvaceae) - Emmanuel Chimeh Ezeako; Abel Yashim Solomon; Hope Chimbuezie Ngozi; Abayomi Oyeyemi Ajagbe; Linus Ogbonnaya Agwu; Lomi Oruchukwu Michael; Evaristus Chinonso Odoh; Victor Inioluwa Olaoye; Philip Nwachukwu Ashiakpa; Martin Benedict Nworie; Vincent E. Ozougwu; Parker Elijah Joshua (International Journal of Plant Based Pharmaceuticals, 2023)
Sida linifolia L. is a valuable plant of West Tropical Africa with several folklore claims and growing evidence of its bioactivity, including its pain-relieving potential; however, scientific validation of these claims is still limited. This study investigated the phytochemical composition and analgesic potential of the ethyl acetate fraction of the hydro-alcoholic extract of S. linifolia leaves (SEAL). Gas chromatography-flame ionization detector (GC-FID) and high-performance liquid chromatography (HPLC) techniques were used to determine the phytochemistry of SEAL. Formalin and acetic acid models were employed to determine the analgesic properties of SEAL. The result of GC-FID analysis revealed varying concentrations of lunamarine, naringenin, ephedrine, catechins, cardiac glycosides, flavanones, kaempferol, flavones, phytate, rutin, steroids, tannins, oxalate, flavan-3-ols, sapogenins, cyanogenic glycosides, anthocyanin, and proanthocyanidins in SEAL. In addition, varying concentrations of polyphenolics, such as phenylacetic acid, caffeic acid, ellagic acid, and naringenin were detected in SEAL via HPLC analysis. The LD50 study showed that SEAL was safe up to 5000 mg/kg body weight per oral (p.o.) in Swiss mice. Pretreatment with oral doses (200, 400, and 600 mg/kg bw) of SEAL significantly (p < 0.05) inhibited all phases of formalin-induced hind paw licking and acetic acid-induced writhing syndrome in mice compared to positive control and was on par with aspirin (100 mg/kg bw p.o.). The observed bioactivity of SEAL could be anchored to its phytoconstituents. Therefore, the plant leaf fraction represents a good source of bioactive compounds with immense potential for exploration in therapeutic research.